Integrating Digital Literacy and Life Skills in Special Education: Evidence from Systematic Literature Review - Rahmat Ariyanto; Budi Susetyo; Endang Rochyadi; Juhanaini Juhanaini; Nofriansyah Nofriansyah; Sapikzal Pratama (Jurnal Pemberdayaan Masyarakat, 2026)
The integration of digital literacy and life skills is essential for developing independent living skills among students with special needs in the digital age. However, despite the growing scholarly interest in integrating digital literacy and life skills for students with special needs, there is a need to explore their implementation in the context of special education. This is to fill the existing knowledge gap in providing evidence-based recommendations to curriculum developers and policymakers. This systematic review is conducted in accordance with the PRISMA 2020 guidelines. A total of 28 studies were selected from 1,847 initial records through a comprehensive screening and quality assessment process by the Mixed Methods Appraisal Tool. The results of the systematic review show positive outcomes in the integration of digital literacy and life skills in the development of independent living skills (85%), social communication skills (78%), and vocational skills (72%). Technology-based approaches, such as mobile applications (64.3%) and assistive technologies (42.9%), were also effective in meeting the needs of students with special needs. The quality of the 28 studies is high, with a mean quality score of 85.4%, indicating high methodological rigor. Theoretically, the systematic review makes a new contribution to the integration of digital literacy and life skills by providing a framework for integrating digital literacy competencies with functional life skills. This is a new contribution to the existing literature, which has so far treated the two constructs in isolation. In practice, the systematic review provides evidence-based recommendations for teachers of students with special needs to undergo digital literacy pedagogy training. In addition, the systematic review recommends that government policy procure assistive technologies through the national education budget. Finally, the systematic review recommends that individualized digital learning plans be part of the support system for students with special needs.